The Right to Litigation as a Prisoner Serving Sentence - Rashid Hamed Al Balushi (Journal of Arts and Social Sciences, 2017)
In the Sultanate of Oman, as well as many other countries around the world, the treatment of prisoners underwent many similar stages of change. The most popular form of punishment was inflicting bodily harm, a punishment solely based on condemning the convicted more than enforcing actual reform and change. This approach in return created an atmosphere of lack of education and knowledge in the prison system, however this situation changed when a new era dawned on the Sultanate, on the 23rd of November 1970, led by His Highness Sultan Qaboos bin Said, providing a new approach to the system of prisons and rule of punishments. This change was brought forth and delegated by the country’s Penal Code 1974/7, Prison Law 94/48, Penal Code Procedures 1999/97s and the Prison law implementing regulations guide 2009/56 on the enforcement of penalties. This research will shed light on the issue of claiming the right to litigate as a fundamental right for prisoners when serving their sentence as the right to bring forth a legal action is one of the most important civil rights a prisoner can have when serving their sentence; a right that is also embedded in the country’s basic statue for every citizen and resident. This involves giving the prisoner access to contact judicial authorities or a defense representative. The research will approach this matter as a whole by clarifying the main issue and factors involved with reference to the law. The research is divided into three main discussion areas, the first being the prisoner’s right to contact judicial authorities for defense during the enforcement of their penalty. The second area will study the prisoner’s right on interpleading in penal enforcement, whilst the third will examine the prisoner’s right to appeal Supreme Court, the right to judicial review made while the prisoner is still serving their current sentence. The research will conclude with my findings as well as recommendations.